\[\boxed{\text{842\ (842).\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[= \left( 4a^{2} + 3 + \left( 7 - 4a^{2} \right) \right)^{2} =\]
\[= \left( 4a^{2} + 3 + 7 - 4a^{2} \right)^{2} = 10^{2} =\]
\[= 100\]
\[100 = 100 \Longrightarrow ч.т.д.\]
\[= (a - 3b)^{2}(a + 3b)^{2} =\]
\[= \left( a^{2} - 9b^{2} \right)^{2} - \left( a^{2} - 9b^{2} \right)^{2} =\]
\[= 0\]
\[0 = 0 \Longrightarrow ч.\ т.\ д.\]
\[\boxed{\text{842.\ }\text{Еуроки\ -\ ДЗ\ без\ мороки}}\]
\[1)\ 7a^{2} - 7b^{2} = 7\left( a^{2} - b^{2} \right) =\]
\[= 7(a - b)(a + b)\]
\[2)\ 3y^{3} - 27y = 3y\left( y^{2} - 9 \right) =\]
\[= 3y(y - 3)(y + 3)\]
\[3)\ m^{5} - m^{3} = m^{3}\left( m^{2} - 1 \right) =\]
\[= m^{3}(m - 1)(m + 1)\]
\[4)\ \frac{49}{64}x^{2}y^{3}z^{6} - 0,04yz^{8} =\]
\[= yz^{6}\left( \frac{49}{64}x^{2}y^{2} - 0,04z^{2} \right) =\]
\[= yz^{6}\left( \frac{7}{8}xy - 0,2z \right)\left( \frac{7}{8}zy + 0,2z \right)\]